Symbiotic Efficiency of Spherical and Elongated Bacteroids in the Aeschynomene-Bradyrhizobium Symbiosis - Lamouche, Florian; Bonadé-Bottino, Nolwenn; Mergaert, Peter; Alunni, Benoit (Frontiers in Plant Science, 2019)
The legume-rhizobium symbiosis is a major supplier of fixed nitrogen in the biosphere and constitutes a key step of the nitrogen biogeochemical cycle. In some legume species belonging to the Inverted Repeat Lacking Clade (IRLC) and the Dalbergioids, the differentiation of rhizobia into intracellular nitrogen-fixing bacteroids is terminal and involves massive cell enlargement and genome endoreduplication, in addition to a strong loss of viability. Moreover, in the Medicago truncatula/Sinorhizobium spp. system, the extent of bacteroid differentiation correlates with the level of symbiotic efficiency. Here, we used different physiological measurements to compare the symbiotic efficiency of photosynthetic bradyrhizobia in different Aeschynomene spp. (Dalbergioids) hosts inducing different bacteroid morphotypes associated with increasing ploidy levels. The strongly differentiated spherical bacteroids were more efficient than the less strongly differentiated elongated ones, providing a higher mass gain to their hosts. However, symbiotic efficiency is not solely correlated with the extent of bacteroid differentiation especially in spherical bacteroid inducing plants, suggesting the existence of other factors controlling symbiotic efficiency.